Feedback from a blended e-learning and simulation training course for operative vaginal delivery. (18th April 2012) - Sullivan, CD; Bahl, R; Strachan, BK
Abstract : Background: Operative vaginal deliveries should be performed by adequately trained practitioners because maternal and neonatal morbidity is inversely related to operator experience and expertise.1 2 It is becoming increasingly important that Obstetric trainees undergo a standardised training package for operative vaginal delivery (OVD). Methods: An interactive e-learning and simulation training course for OVD was developed. 32 ST1's and 2's from Severn Deanery were recruited to participate in the study, of which 27 fully completed the course. Participants had on-line access to the e-learning modules and Consultants or Senior registrars in two hospitals within the region taught small group simulation training sessions, using standardised lesson plans. These were arranged around the participants' and trainers' work commitments (which was difficult to organise). Following completion of training, participants completed feedback questionnaires (Likert scale). Results: 100% of participants thought (agreed or strongly agreed) that the course was interesting, relevant to their training needs and that the e-learning technology increased their access to learning. 96% of participants agreed that the e-learning was easy to use with 93% agreeing that the e-learning complimented the simulation training. 85% agreed/strongly agreed that simulation training within their own hospital was preferable to external courses with two thirds of participants reporting that the simulation sessions were difficult to attend if they had to travel. Discussion: Feedback from this study has shown that trainees found the course interesting and relevant to their practice and that e-learning compliments the simulation training. Trainees preferred simulation training in their own units.